ELECTRONIC CIGARETTE SMOKING EXERTS AN UNFAVOURABLE EFFECT ON AORTIC HEMODYNAMICS AND WAVE REFLECTIONS. (June 2018) - Terentes-Printzios, D.; Ioakeimidis, N.; Vlachopoulos, C.; Abdelrassoul, M.; Georgakopoulos, C.; Gourgouli, I.; Aznaouridis, K.; Solomou, E.; Tousoulis, D.
Abstract : Objective: We investigated the acute effect of electronic cigarette (EC) smoking on the aortic pressure waveform amplification. We also sought to compare the effect of EC and combustible cigarette (TC) smoking on aortic haemodynamics. Design and method: We studied 24 smokers (age: 30 ± 8 years) on 3 separate occasions: a) tobacco cigarette (nicotine content, 1.2 mg) over 5 minutes, b) EC (18 mg E-liquid) for a period of 30 minutes, and c) nothing (sham procedure) for 60 minutes. Smoking EC for 30 min (15 puffs) was chosen to mimic the common pattern of EC smoking. All participants were asked to fill in the Fagerstrom Test for Nicotine Dependence (FTND) that is a standard instrument for assessing the intensity of nicotine dependence. Results: The mean (SD) FTND score of the study population was 3.6 (2.5). Of them, nine were highly nicotine dependent (FTND core>5). There were no significant differences in all baseline measurements between high and low nicotine dependence smokers. Both TC and EC smoking caused a significant increase in brachial pressures and heart rate (HR), and the differences in blood pressure (BP) and HR responses between the two smoking forms were not significant. The aortic pressures also increased significantly after smoking both TC and EC, with the greatest changes seen in the first 5 minutes after TC smoking and 15 minutes EC smoking (figures 1A-C, all P < 0.05). Although AIx, decreased in both two smoking forms, by applying a correction factor for changes in HR, the AIx increased significantly after TC (by 3.0 % at 5 minutes, P < 0.05) and EC (by 2.9% at 15 minutes, P < 0.05) (Figure 1 D). Figure. No caption available. Conclusions: Electronic cigarette smoking exerts an unfavourable and comparable to that of TC smoking acute effect on aortic pressure waveform amplification. Due to the prognostic role of aortic hemodynamics on cardiovascular disease risk, EC could still be considered a hazardous smoking method.